(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
Principles of the work and the results of a survey of the reference stations network on the territory of the RA are described in the article. Information about range on using of the network, as well as on the joint exchange of the network of base stations and the quasigeoid model is included. This survey once again proves the productivity of the technology and advantage over the use of traditional methods. The data presented in the article are obtained by field measurements and their further analysis. Comparison of the obtained data with international data showed that the network of base stations in the Armenia is in compliance with international norms and standards, which makes it possible to conduct research with the help of this network, being sure of the reliability of the data.